The effects of patients' expectations on surgery outcome in total hip and knee arthroplasty: a prognostic factor meta-analysis. Issue 1 (2nd January 2022) - Laferton, Johannes A. C.; Oeltjen, Lara; Neubauer, Karolin; Ebert, David D.; Munder, Thomas
ABSTRACT: Patients' expectations are among the most frequently studied psychological prognostic factors in total knee and hip arthroplasty (TKA/THA). So far, however, evidence on the effect of patients' preoperative expectations on surgery outcome is inconclusive. Heterogeneity of expectation constructs and the use of psychometrically not evaluated measurement instruments have constituted major obstacles for the integration of the current literature. Using a theory-based model of expectation constructs, this meta-analysis set out to disentangle the conflicting results in the current literature. Systematic literature searches yielded k  = 46 studies ( N  = 10, 465) that reported associations of preoperative expectations with postoperative pain, functioning and disability, and satisfaction. Random effects meta-analysis revealed a robust small association ( r  = .16; 95% CI .13, .19) between patients' positive preoperative expectations and better postoperative outcomes. This effect did not differ between THA and TKA, different outcome categories and different follow-up periods. Studies using psychometrically evaluated expectation measures reported significantly higher effects ( r  = .19 ; 95% CI .16, .22). Whether this effect varies among different expectation constructs remains unclear. High-quality studies using validated, multidimensional expectation measures are needed to further understand the role of different expectation constructs in THA and TKA surgery.